Metabolic and ergogenic effects of carbohydrate and caffeine beverages in tennis - Ferrauti, A.; Weber, K.; Struder, H. K. (The Journal of Sports Medicine and Physical Fitness, 1998)
OBJECTIVE: Metabolic and ergogenic effects of carbohydrate and caffeine concentrations, common in commercial available beverages, were investigated in 16 tournament players (8 males and 8 females) during a 4 hrs interrupted tennis match (30 min rest after 150 min). METHODS: On three double-blind occasions players ingested a placebo (PLA), carbohydrate (CHO) or caffeine drink (CAF) at court changeover and during the resting period. In men (women) total intake consisted of 2.8 l (2.0 l) fluid, supplemented with 243 g (182 g) carbohydrates (CHO) or with 364 mg (260 mg) caffeine (CAF), respectively. Postexercise all players performed a ball-machine test (BMT) and a tennis-sprint test (TST). RESULTS: During match play blood glucose (GLU) was higher in CHO and did not differ between CAF and PLA. Immediately after the resting period GLU temporary declined in CHO and PLA, while no significant changes occurred in CAF. Increases of serum FFA and glycerol as well as the decrease of insulin were similar during the PLA and CAF trials and less pronounced in CHO. Postexercise urine concentrations of epinephrine and caffeine were significantly higher in CAF. Perception ratings and hitting accuracy (BMT) were not affected by treatment. CHO resulted in higher blood lactate levels during match play and a better post-exercise sprint performance (TST). Under CAF women won significantly more games than during both other treatments. CONCLUSIONS: CHO enhances tennis-specific running-speed but has no ergogenic effect on tennis performance under the conditions of our study. CAF improves glucose homeostasis at the beginning of work load after rest and may increase tennis success in women.